FINANCIAL REPORTING AND OTHER IMPORTANT ISSUES: NATIONAL AND NATIONAL EXPERIENCE: https://doi.org/10.5281/zenodo.14744664 - Quvvatov , Golibjon (Journal of Contemporary World Studies, 2025)
In this article has been reviewed, the structure and purpose of the financial statements, their classification, national and international experience in the preparation and submission of financial statements, and comparative analysis.